2011
DOI: 10.1007/s00198-011-1544-y
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review on interventions to improve osteoporosis investigation and treatment in fragility fracture patients

Abstract: This study aims to determine osteoporosis (OP) investigation and treatment within post-fracture initiatives conducted in fracture clinics and other orthopedic environments. A systematic review was conducted. Eligibility criteria were: hip fracture patients plus all other fracture patients presenting with a fragility fracture, orthopedic setting where orthopedic physicians/staff were involved, intervention to improve OP management, primary data on ≥20 patients from randomized controlled trials (RCTs) and other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
99
0
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(108 citation statements)
references
References 67 publications
2
99
0
7
Order By: Relevance
“…15 A systematic review found that 65% of clinical systems for ensuring appropriate postfracture care include a dedicated case coordinator. 16 In some countries, a liaison service for fractures has been cost-effective.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…15 A systematic review found that 65% of clinical systems for ensuring appropriate postfracture care include a dedicated case coordinator. 16 In some countries, a liaison service for fractures has been cost-effective.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…95 The current consensus supports more intensive service models of specialist nurse-led services: 10,32 1. Observed differences in hip fracture rates before and after introduction of a fracture prevention service:…”
Section: Introductionmentioning
confidence: 98%
“…No study has used robust outcomes such as refracture rates as highlighted by recent systematic reviews. 95,99 A recent meta-analysis demonstrated a trend towards improved bone mineral density testing rates and treatment initiation. 10,36 However, data on key clinical outcomes are scarce, 100 especially in the context of actual practice conditions in a NHS setting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The systematic review conducted by Sale and colleagues [11] considered published models of case-finding systems in the orthopaedic environment. The reviewers sought to evaluate the structure, protocols, staffing and outcomes of different models and categorise them by the key elements present in each program.…”
mentioning
confidence: 99%